(untitled) (Teología, 2023)
This study examines some principles of interreligious and intercultural dialogue post-Vatican II in South America, particularly in light of the impact of the Nostra Aetate decree. It also explores the principles of Indigenous Theology to recognize the key demands and possibilities for fostering dialogue between Christianity and the indigenous traditions in the region. Additionally, the method called Scriptural Reasoning, currently being employed in Chile, is proposed to promote interreligious and intercultural dialogue among indigenous traditions (specifically Mapuche), Christianity, Islam, and Judaism. The intention of this work is to explore new perspectives and methodological approaches to encourage a more enriching and respectful dialogue.